Representation of systems disturbed by wide band noise - Bashirov, AE; Ugural, S (Pergamon-Elsevier Science Ltd, 2002)
In this paper, a method of handling and working with wide band noise is developed. We represent wide band noise as a distributed delay of white noise and use it to reduce a nonlinear system disturbed by wide band noise to a nonlinear system disturbed by white noise. An application of this reduction to a nonlinear filtering problem under a wide band noise disturbance is discussed. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: wide band noise; white noise; linear stochastic systems